I have to find the Taylor series for the function of a arbitrary poylnomium given by $$ p(x) = a_0 + a_1x + ... + a_{k-1}x^{k-1}+a_kx^k $$ By a few calculations I have realized that the Taylor series is just \begin{align*} \sum_{n = 0}^\infty \frac{p^{(n)}(a)}{n!}(x-a)^n & = p(a) + p'(a)(x-a) + \frac{p''(a)}{2!}(x-a)^2 + ... + \frac{p^{(n)}}{n!}(x-a)^n \\ & = a_0 + a_1(x-0)^1 + 2!\frac{a_2}{2!}(x-0)^2 + ... + n!\frac{a_k}{n!}(x-0)^n \\ & = a_0 + a_1x + a_2x^2+...+a_kx^n \end{align*} if I have not made any mistakes. Is this correct? Furthermore I now have to argue/prove that if $x_0 \in \mathbb{R}$ and $T_n(x)$ is a Taylor polynomium for p of grade $n$ about $x_0$ that $T_n(x) = p(x)$ for all $x \in \mathbb{R}$ when $n \geq k$. I have divided this into two scenarios. When $n > k $ and when $n = k$.

When $n = k$ I have just proven this in a) so I have said this is obvious. But I am not sure how to handle the last part when $n > k $. Can you help me in the right direction?

Lastly I have to find a function $f: ]-1,1[ \rightarrow \mathbb{R}$ which Taylor series about $0$ is equal to the series given by $$ 2 + 2x + 2x^2 + 2x^3 +...+2x^n $$ Is this just $$ f(x) = 2 + 2x^2 + 2x^3 + ... + 2x^n $$ in continuation of the the part I have to prove? Otherwise I am not sure what to do.

Thanks in advance for your help.



  • 1
    $\begingroup$ Remember that the idea behind Taylor series is to find the polynomial which is the best approximation for a given function. When the function is not a polynomial, the series gives better and better approximations as you take more and more terms. So the best approximation to a polynomial is itself. $\endgroup$ Mar 22 '20 at 14:06

Let $ k\in\mathbb{N} $, and $ p\left(x\right)=\sum\limits_{j=0}^{k}{a_{j}x^{j}} $, we know that for any $ i\leq k $, we have $ p^{\left(i\right)}\left(x\right)=\sum\limits_{j=i}^{k}{a_{j}\frac{j!}{\left(j-i\right)!}x^{j-i}}\cdot $

Thus, for any real $ a $, we get :\begin{aligned} p\left(x\right)&=\sum\limits_{j=0}^{k}{a_{j}\left(a+x-a\right)^{j}}\\&=\sum\limits_{j=0}^{k}{a_{j}\sum\limits_{i=0}^{j}{\binom{j}{i}a^{j-i}\left(x-a\right)^{i}}}\\&=\sum\limits_{i=0}^{k}{\sum\limits_{j=i}^{k}{a_{j}\binom{j}{i}a^{j-i}\left(x-a\right)^{i}}} \\&=\sum\limits_{i=0}^{k}{\frac{1}{i!}\left(\sum\limits_{j=i}^{k}{a_{j}\frac{j!}{\left(j-i\right)!}a^{j-i}}\right)\left(x-a\right)^{i}}\\p\left(x\right)&=\sum\limits_{i=0}^{k}{\frac{p^{\left(i\right)}\left(a\right)}{i!}\left(x-a\right)^{i}} \end{aligned}

(In the third line, we switched the order of the double summation)


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.